Research of adaptive web design principles - Егорова, Ирина Николаевна; Толстая, Екатерина Александровна (Eastern-European Journal of Enterprise Technologies, 2012)
Due to the development of mobile technology in recent years more and more people use their phones to access the Internet. However, such peculiarities of mobile devices, as small size of the display and touch interface make it inconvenient to view general websites on the screen. The authors suggested a solution to this problem - the creation of adaptive Website. The adaptive web design is a technology of site creation that provides easy viewing on a variety of devices: desktops, laptops, tablets, smartphones. The article concerns the development of an adaptive web site, oriented towards the users of mobile devices. The basic principles that have the greatest influence on the efficiency of the final product are: flexible grid, flexible images and media queries. The results obtained were used to develop a training website